Quality standards for immunobiological medicinal products - new texts in the State Pharmacopoeia of the Russian Federation - A. A. Movsesyants; V. P. Bondarev; Yu. V. Olefir; V. A. Merkulov; L. F. Shimchuk (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Analysis of XI and XII editions of the State Pharmacopoeia of the Russian Federation proved the necessity and relevance of elaborating quality standards for immunobiological medicinal products as well as methods of their control. Assurance of safety and efficacy of this group of medicines could be achieved only by fulfilling the requirements of modern standards of quality and assuming that methods used for assessment of quality parameters of biologicals are adequate and informative. Top priorities addressed during the preparation of the XIII edition of the State Pharmacopoeia of the Russian Federation were: systematization of quality standards for biologicals on the basis of product types and methods of analysis, and harmonization of requirements for quality parameters with those of the leading world pharmacopoeias, primarily with the European Pharmacopoeia.